QSAR Studies of 1,2-Cyclomethylene Carboxylic Monoamide Hydroxamic Derivatives - Galpalli, N.D.; Chaturvedi, S.C. (Asian Journal of Chemistry, 2016)
A series of monoamide derivatives of cis and trans-1,2-cyclohexane dicarboxylic acids bearing hydroxamic group in the side chain molecules as potential ACE inhibitors were subjected to QSAR analysis. The QSAR equations indicate that mostly electronic and shape parameters are responsible for the variation in biological activity. Molecular shape analysis suggests that there is less difference in NCOSV while comparing biological activity with reference compound. The so obtained and validated models bring important structural insight to aid the design of novel class of non-amino acid ACE inhibitors.